2022
DOI: 10.14719/pst.1728
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of maize genotypes performance under water deficit using ISSR molecular index

Abstract: Shortage of water is disastrous for crop production. The aim of this work is to obtain a group of maize inbred lines and hybrids that tolerates water deficit and collecting molecular characterizations for selection. This work was conducted in the 2019 and 2020. Five maize pure inbred lines B73, A132, NA30, S7 and DR-B1 were planted according to the design of half-diallel cross-breeding of the second Griffing method, and then 10 hybrids and 5 inbred lines were planted under the impact of irrigation intervals of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The values of σp and C.V% were low at the density of 88.88 thousand plants ha -1 , reaching 105.1 and 9.123. These results agree with [01], [13], [1], [14], [15], [16]. The results of the study showed that there was a significant interaction between genotype and plant density, the Haisin selected genotype gave the highest number of seeds per disk, reaching 1597.8 seeds at a plant density of 53.33 thousand plants ha -1 , while the Haisin original genotype gave the lowest number of seeds per disk, at 1028.0 seeds at a plant density of 88.88 thousand plants ha -1 .…”
Section: Seeds Per Disksupporting
confidence: 92%
“…The values of σp and C.V% were low at the density of 88.88 thousand plants ha -1 , reaching 105.1 and 9.123. These results agree with [01], [13], [1], [14], [15], [16]. The results of the study showed that there was a significant interaction between genotype and plant density, the Haisin selected genotype gave the highest number of seeds per disk, reaching 1597.8 seeds at a plant density of 53.33 thousand plants ha -1 , while the Haisin original genotype gave the lowest number of seeds per disk, at 1028.0 seeds at a plant density of 88.88 thousand plants ha -1 .…”
Section: Seeds Per Disksupporting
confidence: 92%
“…The (Line × Tester) approach was employed for this purpose. Suggested by [17] and proven by [18,19] by the implementation of a randomized full block design with four replications. Throughout the two growing seasons, all necessary tasks were performed to support the crop, such as plowing at right angles, smoothing the soil, leveling the ground, providing irrigation, and removing weeds, in accordance with the prescribed scientific guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, approximating the average degree of dominance enables one to ascertain the genetic mechanism governing the traits, thereby facilitating the identification of the most effective breeding technique to enhance them. Regarding the combining characteristics that have been the subject of investigation by numerous yellow maize crop researchers [1][2][3][4], they have discovered that special ability has a more substantial impact than general ability. Genetic variation is crucial for plant cultivators because it provides a broad spectrum from which to select genetic variation, which serves as the foundation from which the most effective genetic combinations can be derived.…”
Section: Introductionmentioning
confidence: 99%
“…It was quite similar to the 160 kg ha -1 seeding rate, with the exception that the 100 kg ha -1 seeding rate resulted in the slowest growth rate of 11.86 g m -2 day -1 . An increase in net photosynthesis and plant growth rate is caused by an increase in the leaf area index and light interception efficiency, which are both enhanced when the green cover is completed early at high seeding rates [17,18]. The research components showed a substantial interaction, with the variety Baraq showing the best results at a seeding rate of 190 kg ha -1 and an average growth rate of 15.07 g m -2 day -1 .…”
Section: The Crop Growth Rate (Cgr) In G M -2 Day -1mentioning
confidence: 99%
“…With an average of 22.49%, the Amal variety was the lowest. Due to its higher grain production and lower biological yield value [17], the IPA 265 variety outperforms its competitors in harvest index. This is because genotypes differ in how efficiently they transport the end products of photosynthesis from leaves to sink organs.…”
Section: Harvest Indexmentioning
confidence: 99%